2009
DOI: 10.1111/j.1365-2133.2008.08923.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety and efficacy of topical prostaglandin E2in treatment of vitiligo

Abstract: The efficacy and safety of topical PGE2 make it a promising therapy for localized stable vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 4 publications
8
41
3
Order By: Relevance
“…Our study was designed to evaluate efficiency of combination of narrowband ultraviolet B (NB‐UVB) and topical latanoprost on repigmentation of lesions in hard‐to‐repigment locations as well as additional benefits of microneedling prior to topical application of latanoprost. The combination of the above treatment modalities was selected due to several reasons: Although data on prostaglandin use in vitiligo treatment are modest, therapeutic results are encouraging , and latanoprost combined with NB‐UVB is superior over either one ; Needling is used for treating localized vitiligo alone or in combination with NB‐UVB with quite satisfying therapeutic results . Up to now, nobody investigated microneedling with Dermaroller ® , an improved device for needling with controlled needle penetration depth, as a vitiligo therapeutic modality ; NB‐UVB is considered as a “golden standard” in vitiligo treatment with high repigmentation rate, which is further increased when combined with other therapeutic options . …”
Section: Introductionmentioning
confidence: 99%
“…Our study was designed to evaluate efficiency of combination of narrowband ultraviolet B (NB‐UVB) and topical latanoprost on repigmentation of lesions in hard‐to‐repigment locations as well as additional benefits of microneedling prior to topical application of latanoprost. The combination of the above treatment modalities was selected due to several reasons: Although data on prostaglandin use in vitiligo treatment are modest, therapeutic results are encouraging , and latanoprost combined with NB‐UVB is superior over either one ; Needling is used for treating localized vitiligo alone or in combination with NB‐UVB with quite satisfying therapeutic results . Up to now, nobody investigated microneedling with Dermaroller ® , an improved device for needling with controlled needle penetration depth, as a vitiligo therapeutic modality ; NB‐UVB is considered as a “golden standard” in vitiligo treatment with high repigmentation rate, which is further increased when combined with other therapeutic options . …”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E2 (PGE2) has been shown to have immunomodulatory effect and play an important role in melanogenesis, having growth‐stimulatory effects on melanocytes and being capable of regulating their proliferation and maturation. In animal models, the topical application of PGE2 has been shown to increase melanocyte density , while lately, an observational study on humans showed significant results when a gel formulation containing PGE2 was topically applied twice daily for 6 months in subjects with stable vitiligo patches involving <5% body surface area . These positive results were also supported by evidence that UV light exerts a major part of its therapeutic efficacy in vitiligo by the increased production of PGE2 .…”
Section: Prostaglandin E2 (Pge2) Analogsmentioning
confidence: 96%
“…A transient burning sensation was the most common adverse effect, which was seen in 18% of the patients. 21 …”
Section: Autacoids Lipid Derivedmentioning
confidence: 97%
“…Prostaglandin E 2 (PGE 2 ) is one of the biologically active derivatives of 20 carbon atom polyunsaturated essential fatty acids released from cell membrane phospholipids. 21 Topical PGE 2 application has been demonstrated to improve flap survival in random-pattern skin flaps in rats, 22 presumably by acting as a potent topical vasodilator. 23 PGE 2 -induced iris darkening, hyperpigmentation of eyelashes, and periocular hyperpigmentation have been reported, presumably by a direct or secondary messenger-mediated interaction with melanocytes.…”
Section: Autacoids Lipid Derivedmentioning
confidence: 99%